ความฉลาดทางอารมณ์ของพลทหารใหม่ในสังกัดกองทัพเรือ - โสภิดา ล่อใจ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This purpose of this research was to study the relationship between personality and emotional intelligence of the naval recruits in the Royal Thai Navy. This study was conducted with a sample size of 400 recruits. The instruments used were personal questionnaires, personality tests and emotional intelligence evaluation forms. Data was analyzed using percentage, mean and standard deviation. The relationship between these variables was discovered using unpaired t-tests, ANOVA Relation among personality test as well as the Pearson s Product Test. The results revealed that the test group consisted mostly of males between the ages of 21 and 29, had high school education, were single, had introverted personalities and were almost as equally stabile as they were neurotic. It was found that the emotional intelligence of the Navy Recruits was average overall. Personalities of the Naval Recruits were very much related with their emotional intelligence. Scale-E had no relation with respects to emotional intelligence(r = 0.223, statistical significance p<.001) and Scale-N was inversely related with emotional intelligence(r= -0.366, statistical significance p <0.01), religion, previous work experience, income and quality of their naval training all had statistical significance with respects to emotional intelligence (p<.001). Furthermore, family relationships were found to be significant with respects to emotional intelligence (statistical significance p<.05) as was physical endurance and mental stability (p<.01).